Pemikiran Dan Implementasi Pemikiran Bj. Habibie Dalam Mengatsi Krisis Ekonomi Indonesia - Tatebburuk, Bonivasius (Journal of Society Bridge, 2024)
Indonesia's economy experienced a monetary crisis during President Soeharto's administration, which occurred between 1997-1998 and led to various economic problems that eventually resulted in his resignation. Leadership then shifted to B.J. Habibie, who worked hard to restore the national economy through his economic policies. President B.J. Habibie focused his efforts on strengthening and recovering the economy after the monetary crisis. Although there were signs of improvement, such as a decrease in inflation and an appreciation of the rupiah against the US dollar, consumer purchasing power remained low, and public trust in the president declined as he was still seen as part of the New Order regime.